Media Flipbook Based on Heyzine Application by Elementary School Teachers in Supporting Interactive Learning - Khusnul Fatonah; Muhammad Rijal Fadli; Irma Savitri Sadikin; Mujazi Mujazi (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah kendari, 2025)
This study aims to analyze the quality of flipbook media created by elementary school teachers using the Heyzine application as a tool to support interactive learning. Using a qualitative approach and content analysis method, this research examines 10 flipbooks developed by teachers at SD Penggilingan 01 Jakarta. Data were collected through product analysis, interviews with teachers, principals, and students, as well as classroom observations. The findings reveal that most teachers were able to design flipbooks with clear structure, engaging visuals, and interactive features such as navigation buttons, audio, video, and animation. These media enhanced students’ engagement and motivation in learning. However, several limitations were identified, especially in optimizing advanced features like animation and interactive quizzes. This study highlights the importance of continuous digital literacy training for teachers to fully utilize educational technology. The integration of teacher-created digital media like flipbooks represents a promising step toward learner-centered and interactive teaching practices in elementary education.